Genetic diversity and biogeography of native and introduced populations of Ulva pertusa (Ulvales, Chlorophyta). Issue 2 (April 2016) - Hanyuda, Takeaki; Heesch, Svenja; Nelson, Wendy; Sutherland, Judy; Arai, Shogo; Boo, Sung Min; Kawai, Hiroshi
SUMMARY: Genetic diversity of native and introduced populations of Ulva pertusa (Ulvales, Chlorophyta) was examined using genetic markers of chloroplast, mitochondria and nuclear non‐coding region sequences. In the preliminary investigations to genetically identify the species for further analyses, U. pertusa was found only from temperate coasts of the more extensive collection sites including tropical coasts suggesting that it is a temperate species and basically not distributed in tropical regions. For chloroplast and mitochondrial sequences, repeating patterns of short tandem repeat sequences and nucleotide substitutions were used to recognize the haplotypes (genetic types). A total of 48 haplotypes based on combinations of chloroplast and mitochondrial haplotypes were recognized in the 244 specimens collected in the presumptive native range (Northeast Asia) and introduced populations (North America, Australia, New Zealand, Chile and Europe). Among them, 46 haplotypes (H1–H8 and H11–H48) were recognized in Northeast Asia, whereas only 1–5 haplotypes were recognized in the other areas. Nuclear microsatellite sequences were also analyzed. The lengths of the PCR products including the nuclear microsatellite region of 234 specimens were determined, and a total of 17 genotypes were recognized. Among them, 14 genotypes were found in Northeast Asia, whereas 1–7 genotypes were recognized in the other areas. Based on the results, the hypothesis that the native range of the species is in Northeast Asia was supported, and the populations outside this range were concluded to be non‐indigenous populations.